Pregunta
Ive for \( f \). \( -2=-2(f+2) \) \( f=\square \) Submit
Ask by Estrada Burton. in the United States
Feb 03,2025
Solución de tutoría real
Respuesta verificada por el tutor
Responder
\( f = -1 \)
Solución
Solve the equation \( -2=-2(f+2) \).
Solve the equation by following steps:
- step0: Solve for \(f\):
\(-2=-2\left(f+2\right)\)
- step1: Swap the sides:
\(-2\left(f+2\right)=-2\)
- step2: Change the sign:
\(2\left(f+2\right)=2\)
- step3: Divide both sides:
\(\frac{2\left(f+2\right)}{2}=\frac{2}{2}\)
- step4: Divide the numbers:
\(f+2=1\)
- step5: Move the constant to the right side:
\(f=1-2\)
- step6: Subtract the numbers:
\(f=-1\)
The solution to the equation \( -2=-2(f+2) \) is \( f=-1 \).
Revisado y aprobado por el equipo de tutoría de UpStudy
Como
error msg
Explicar
Simplifique esta solución
Extra Insights
Let's solve the equation step by step. Starting with the equation, we can first divide both sides by -2, which simplifies to: \( 1 = f + 2 \). Next, we subtract 2 from both sides to isolate \( f \): \( f = 1 - 2 \) which gives us \( f = -1 \). So, the value of \( f \) is \( -1 \).
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium